Measurement of the energy spectrum of cosmic rays at the highest energies using data from Pierre Auger Observatory - Mariş Ioana C. (EPJ Web of Conferences, 2013)
We report a measurement of the flux of cosmic rays with unprecedented precision and statistics using data from the Pierre Auger Observatory. Based on fluorescence observations in coincidence with at least one station of the surface detector we derive a spectrum for energies above 1018 eV. We also report on the energy spectra obtained with the surface detector array. The spectral features are presented in detail and the impact of systematic uncertainties on these features are addressed.